(untitled) - Haskins, Jim (Hoboken, N.J., 2003)
Discover why young people all over the country are reading the Black Stars biographies of African American heroes.
Keywords: Trung tâm Học liệu ĐHCT,African American abolitionists,African Americans; Biography,History; 1863-1877